Online Education, International Cooperation and Sustainable Development in Sudan - Alcaide, Jorge Carlos Naranjo; Greco, Sabrina (Social Education Research, 2023)
This article describes three online learning experiences carried out between 2017 and 2021 by Comboni College of Science and Technology, a Sudanese higher education institution in a context characterized by frequent power cuts, irregular and limited internet access, lack of preparedness of the teaching staff, and very limited digital skills among students. These educational interventions consisted of two international cooperation projects and a learning experience through Moodle during the COVID-19 lockdown, from which it was possible to collect data on students' performance and compare it with data obtained under ordinary conditions using a paired sample t-test. The research analyzes these three online educational interventions, the context in which they took place, and their subsequent outcomes within the framework of the relationship between higher education, human capital development, and job insertion. The study reveals that, in addition to connectivity problems inherent to the context, some soft skills, such as time management and familiarity with using an e-mail account, should be considered in the selection or training of learners. The research also indicates that any international e-learning project in a Least Developed Country (LDC) should account for the fact that most students do not own a personal laptop and access the internet primarily through their smartphones. Moreover, students in Information and Communication Technologies (ICT)–based university programs show a better predisposition for online programs than others. The study highlights the importance of computer literacy courses in the first semester of undergraduate programs for non-ICT programs and of the presence of a physical tutor to ensure the success of any international educational project, even for students in ICT-based university degrees, which may be particularly relevant once the ongoing war ends and the field becomes open for international cooperation in education.